Synthesis, structure, and biological properties of a Co(II) complex with tridentate Schiff base ligand. Issue 10 (19th May 2018) - Jana, Kalyanmoy; Das, Somnath; Maity, Tithi; Hossain, Maidul; Chandra Debnath, Subhas; Chandra Samanta, Bidhan; Seth, Saikat Kumar
Abstract: A new Co(II) complex of general formula [Co(L)2 ] has been synthesized from a NNO tridentate Schiff base ligand, 2-[(piperidin-2-ylmethylimino)-methyl]-phenol (L). The title complex is characterized by elemental, spectroscopic, antibacterial, and single crystal X-ray structural studies. X-Ray crystallography reveals that the complex shows a distorted octahedral geometry around the Co(II) ion. The complex was tested against several bacteria and shows good antibacterial activities against almost all of the bacteria. The interactions of the title complex with calf thymus deoxyribonucleic acid (CT-DNA) have been investigated by electronic absorption and fluorescence spectroscopy, showing that the complex interacts with CT-DNA via partial intercalation. Thermogravimetric analysis (TGA) of the complex has also been reported and the result shows that the complex is thermally stable up to 134 °C. Abstract :